MANFAAT PEMANASAN STATIS DAN DINAMIS SERTA PENDINGINAN BAGI SISWA DI SD NEGERI 101740 TANJUNG SELAMAT - Ginting, Refa Ivana Br; Agustina , Citra; Aritonang , Kornelis; Pakpahan , Anjeli Agustina; Sembiring , Heka Maya Sari Br (PUAN INDONESIA, 2025)
This study examines the impact and benefits of warm-up (static and dynamic) and cool-down activities to prevent injuries during physical exercise. Emphasizing their role in enhancing circulation and body readiness, the program—titled "Strategies to Improve Understanding of the Importance of Warm-up and Cool-down at SDN 101740 Tanjung Selamat"—aims to increase student awareness and proper practice of these routines. Many elementary students overlook warm-up and cool-down exercises, resulting in potential injuries and reduced performance. To address this, the service initiative was designed to educate students and teachers about effective techniques and their health benefits. The program included discussions, demonstrations, and hands-on training across several sessions. Key topics covered proper static and dynamic warm-up methods, cool-down procedures, and their relevance to physical health and performance. Findings indicate enhanced student understanding, reduced injury risk, and increased enthusiasm for sports participation. The initiative underscores the need for structured and engaging physical education that prioritizes injury prevention and performance optimization.